CE: Original Research. (May 2016) - Geiger-Brown, Jeanne; Sagherian, Knar; Zhu, Shijun; Wieroniey, Margaret Ann; Blair, Lori; Warren, Joan; Hinds, Pamela S.; Szeles, Rose
Abstract : N/A: Background: Nurses who work the night shift often experience high levels of sleepiness. Napping has been adopted as an effective countermeasure to sleepiness and fatigue in other safety-sensitive industries, but has not had widespread acceptance in nursing. Purpose: To assess the barriers to successful implementation of night-shift naps and to describe the nap experiences of night-shift nurses who took naps. Methods: In this two-hospital pilot implementation project, napping on the night shift was offered to six nursing units for which the executive nursing leadership had given approval. Unit nurse managers' approval was sought, and where granted, further explanation was given to the unit's staff nurses. A nap experience form, which included the Karolinska Sleepiness Scale, was used to assess pre-nap sleepiness level, nap duration and perceived sleep experience, post-nap sleep inertia, and the perceived helpfulness of the nap. Nurse managers and staff nurses were also interviewed at the end of the three-month study period. Results: Successful implementation occurred on only one of the six units, with partial success seen on a second unit. Barriers primarily occurred at the point of seeking the unit nurse managers' approval. On the successful unit, 153 30-minutes naps were taken during the study period. A high level of sleepiness was present at the beginning of 44% of the naps. For more than half the naps, nurses reported achieving either light (43%) or deep (14%) sleep. Sleep inertia was rare. The average score of helpfulness of napping was high (7.3 on a 1-to-10 scale). Nurses who napped reported being less drowsy while driving home after their shift. Conclusion: These data suggest that when barriers to napping are overcome, napping on the night shift is feasible and can reduce nurses' workplace sleepiness and drowsy driving on the way home. Addressing nurse managers' perceptions of and concerns about napping may be essential to successful implementation. Abstract : Although napping is used to reduce sleepiness and fatigue in other safety-sensitive industries, it has not had widespread acceptance in nursing. Here the authors describe the results of a project they conducted to assess the barriers to successful implementation of night-shift naps and to describe the nap experiences of night-shift nurses.